A new species of Hydrodynastes Fitzinger, 1843 from central Brazil (Serpentes: Colubridae: Xenodontinae) - Franco, Francisco L.; Fernandes, Daniel S.; Bentim, Bruno M. (Zootaxa, 2007)
A new species of Hydrodynastes is described from the State of Tocantins, Central Brazil. The new species is distinguished from all congeners by having a melanistic color pattern, with head and dorsum of the body mostly dark-brown to black; absence of postocular stripe; venter grayish-brown, with dark rounded blotches outlining two lateral stripes which become gradually paler towards the posterior region of the belly, disappearing after midbody. Comparisons of the new species are made with others species of the genus and its affinity with H. gigas is suggested based on meristic and hemipenial characters